Birthweight as a measure of holiday stress. Issue 3 (16th March 2018) - Sohn, Kitae
ABSTRACT: Young wives in South Korea often dread New Year's Day and Thanksgiving Day because they assume the burden of cooking, cleaning, and other household chores. We used their offspring's birthweight as an indicator of their stress levels. We included all Korean singletons born in hospitals during 1997–2014 ( N =  8, 589, 426) and regressed birthweight on in utero holiday experience by trimester, along with covariates. Babies who experienced New Year's Day in the first trimester were 9.4 grams lighter than those who did not; the amount is equivalent to 120% of the reduced birthweight associated with experiencing landmine explosions during the first trimester in Colombia. Higher birthweight was related to being in the first trimester during Thanksgiving Day versus not. However, experiencing this holiday during the third trimester was associated with less increase in birthweight than during the other trimesters. These results suggest that the New Year's holiday may reflect stress for Korean women in their first trimester of pregnancy, resulting in reduced birthweight, but similar stress was not associated with the Thanksgiving Day holiday. Clinicians and policymakers should be aware of this potential high stress level among Korean women during New Year's Day and seek ways to prevent and alleviate it.